Letramento matemático através de jogos e prática. - SOUSA, Ilza de Jesus Alves Correa (2025)
This is an exploratory study with a qualitative approach, involving a literature review and empirical research, aiming to investigate academic sources regarding mathematical literacy through games. The study explores topics related to the strategies employed by teachers to promote mathematical literacy and enhance students’ understanding in classrooms through the use of games. After material selection and identification of relevant topics,the study qualitatively analyzes the importance of mathematical literacy in education,examining the strategies employed by teachers to make mathematics more enjoyable in the classroom, particularly through the use of games. A critical analysis of the articles reveals that games can be effective tools for students, fostering mathematical learning, enhancing the understanding of mathematical concepts, and developing cognitive skills. However, it is crucial to note that the introduction and use of games should be pedagogically grounded and carefully planned by teachers, ensuring a more effective learning experience.